Research of reactive ion and plasma-chemical etching effect on diamond coating surface morphology; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Okhotnikov V. V. Vitaly Vladimirovich (High energy processes and external exposure of materials, 2016)
Title screen